Correction: Cesium carbonate mediated C–H functionalization of perhalogenated 12-vertex carborane anions. Issue 45 (24th May 2022) - Lovera, Sergio O.; Bagdasarian, Alex L.; Guo, Juchen; Nelson, Hosea M.; Lavallo, Vincent
Abstract : Correction for 'Cesium carbonate mediated C–H functionalization of perhalogenated 12-vertex carborane anions' by Sergio O. Lovera et al., Chem. Commun., 2022, 58, 4060–4062, DOI: ; https://doi.org/10.1039/D2CC00173J .